2009
DOI: 10.1121/1.3224830
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced bubble jetting into a viscous fluid with application to tissue injury in shock-wave lithotripsy

Abstract: Shock waves in liquids are known to cause spherical gas bubbles to rapidly collapse and form strong re-entrant jets in the direction of the propagating shock. The interaction of these jets with an adjacent viscous liquid is investigated using finite-volume simulation methods. This configuration serves as a model for tissue injury during shock-wave lithotripsy, a medical procedure to remove kidney stones. In this case, the viscous fluid provides a crude model for the tissue. It is found that for viscosities com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Thus far, the shock wave-bubble interaction has been studied with several numerical methods (Calvisi et al 2008, Freund et al 2009, Johnsen and Colonius 2008, 2009, Takahira et al 2008, 2009). Calvisi et al (2008) calculated the bubble collapse near a rigid boundary using the boundary integral method and clarified that the bubble collapse process with the formation of liquid jet depends on the distance of the bubble relative to the wall when the reflection of the incident wave is taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the shock wave-bubble interaction has been studied with several numerical methods (Calvisi et al 2008, Freund et al 2009, Johnsen and Colonius 2008, 2009, Takahira et al 2008, 2009). Calvisi et al (2008) calculated the bubble collapse near a rigid boundary using the boundary integral method and clarified that the bubble collapse process with the formation of liquid jet depends on the distance of the bubble relative to the wall when the reflection of the incident wave is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Calvisi et al (2008) calculated the bubble collapse near a rigid boundary using the boundary integral method and clarified that the bubble collapse process with the formation of liquid jet depends on the distance of the bubble relative to the wall when the reflection of the incident wave is taken into account. Freund et al (2009) investigated the problem using the finite volume method. They found that the viscous resistance in tissues can significantly suppress the penetration of the liquid jet induced by the bubble collapse.…”
Section: Introductionmentioning
confidence: 99%
“…When De 1/Re, the time derivative of stresses in Eqs. (9) and (10) is negligible compared to the rest of the terms. A linear analysis is sufficient to obtain the asymptotic solution.…”
Section: B Multiple Scales Perturbation Analysismentioning
confidence: 99%
“…Fluids 25, 083101 (2013) tissue lies in the viscoelastic, compressible, and multiphase nature of the problem. Direct simulations of the compressible equations of motion have been performed to study single-bubble dynamics in biomedical applications, many of which have been restricted to inviscid [5][6][7][8] and Newtonian 9 simulations. The few direct simulations in a viscoelastic medium are based on Maxwell fluids, none in which compressibility is included, preventing accurate studies of large-amplitude oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] In addition, shock-wave induced bubble collapse and jetting near a liquid-solid interface have been studied via direct solution of the Navier-Stokes equations. 21, 22 Blake et al studied bubble deformation near a rigid boundary 23 and a free surface. 24 Modeling the system with the boundary element method (BEM), they found that the liquid jet is directed away from the free surface.…”
Section: Introductionmentioning
confidence: 99%